2006
DOI: 10.1016/s1472-6483(10)61993-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated day 3 FSH/LH ratio due to low LH concentrations predicts reduced ovarian response

Abstract: Adequate ovarian response, essential for successful IVF, cannot be accurately predicted. This study retrospectively reviewed all patients undergoing IVF from 1998 to 2001. Inclusion criteria were age <41 years at treatment onset and a basal day 3 serum FSH concentration <12 IU/l. Women with FSH or=3 in group 1 and <3 in group 2 (controls). Age at treatment initiation, basal serum day 3 FSH and LH concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
6
27
1
1
Order By: Relevance
“…Also, this study finds an increase in LH/FSH ratio effect on IVF outcome is similar to that by Barroso et al [7] and Shrim et al [10], which reported similar results in patients with elevated LH/FSH ratio >3. Also from this study, GnRHa (Gonapeptyl.01 ® ) has better effectiveness (114%) on total number of oocytes retrieved than other triggering medicine as well as similar effectiveness in stimulating oocytes maturation as uHCG (75% to 81%) which is in agreement with the concept by Shahar and Peter, 2013 which suggested that a 0.2 mg of gonadotrophin-releasing hormone agonist (GnRHa) can replace human chorionic gonadotrophin (HCG) as a trigger of final oocyte maturation and that GnRHa trigger offers important advantages, including significant prevention of ovarian hyperstimulation syndrome (OHSS), safety and comfort of patients.…”
Section: Discussionsupporting
confidence: 91%
“…Also, this study finds an increase in LH/FSH ratio effect on IVF outcome is similar to that by Barroso et al [7] and Shrim et al [10], which reported similar results in patients with elevated LH/FSH ratio >3. Also from this study, GnRHa (Gonapeptyl.01 ® ) has better effectiveness (114%) on total number of oocytes retrieved than other triggering medicine as well as similar effectiveness in stimulating oocytes maturation as uHCG (75% to 81%) which is in agreement with the concept by Shahar and Peter, 2013 which suggested that a 0.2 mg of gonadotrophin-releasing hormone agonist (GnRHa) can replace human chorionic gonadotrophin (HCG) as a trigger of final oocyte maturation and that GnRHa trigger offers important advantages, including significant prevention of ovarian hyperstimulation syndrome (OHSS), safety and comfort of patients.…”
Section: Discussionsupporting
confidence: 91%
“…diminished ovarian reserve and poor IVF outcome [7][8][9][10][11][12]. However, in the studies investigating the impact of elevated FSH/LH ratio as a predictor of prognosis in IVF success, analysis according to age was not performed.…”
Section: Introductionmentioning
confidence: 99%
“…13,17,24 It is of note that a number of the studies have moved to reiterate the importance of generating individualized data from centres in terms of using LH as it seems likely that the available data is not universally applicable due to factors such as the heterogeneity of individual patient populations, laboratory assays which themselves show inter laboratory variation of LH quantification and stimulation protocols. 17,21,24 For the purposes of establishing LH as an ORT, these findings need to be viewed in line with the current opinion and controversies surrounding ORTs and their value. In order to give further context to these issues, we use two ovarian markers which look the most promising in becoming established as the 'ideal' markers of ovarian reserve -Antimüllerian hormone (AMH) and the antral follicle count (AFC) -as reference points.…”
Section: Discussionmentioning
confidence: 99%
“…There was still a statistically significant reduction in cycle outcomes. 17 Orvieto et al payed special attention to patients undergoing both agonist (n = 131) and GnRH antagonist (n=137) protocols , and once again both subgroups achieved lower pregnancy rates in contrast to their controls (11.1 vest 27.7 and 8.3 vs. 31.9) with FSH/LH ratios >2 or >3. It is of note that the FSH/ LH ratio still maintained its discriminative ability in this population who were selected on the premise that they had a favourable prognosis for ART (women <35 years of age with day 3 FSH <15IU/L undergoing up to their 3 rd IVF cycle).…”
Section: The Evidence For Lh As a Marker Of Ovarian Reservementioning
confidence: 99%
See 1 more Smart Citation